2012
DOI: 10.1029/2011gl050691
|View full text |Cite
|
Sign up to set email alerts
|

The Wrangel Island Polynya in early summer: Trends and relationships to other polynyas and the Beaufort Sea High

Abstract: Polynyas, regions of reduced sea ice concentration relative to their surroundings, are important features of the polar climate system in which enhanced fluxes of heat, moisture, and momentum can occur between the atmosphere and ocean. As such, they play a significant role in many atmospheric, oceanographic and biological processes. There are concerns that in a warming climate, in which there is a trend towards a reduction in sea ice cover, that the location, size and duration of many polynyas may change result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…They found that an enhanced summer anti‐cyclonic circulation associated with a stronger BSH occurs in years with reduced September sea ice extent, with the opposite occurring in years with a weaker BSH. Furthermore, Moore and Pickart [2012] identified early summer polynyas in the Chukchi Sea, including the Wrangel Island polynya, that were associated with a stronger BSH and enhanced easterly flow across the region. The BSH also plays an important role in forcing the Beaufort Gyre, an oceanographic feature that is the Arctic Ocean's largest reservoir of freshwater [ Giles et al , 2012].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that an enhanced summer anti‐cyclonic circulation associated with a stronger BSH occurs in years with reduced September sea ice extent, with the opposite occurring in years with a weaker BSH. Furthermore, Moore and Pickart [2012] identified early summer polynyas in the Chukchi Sea, including the Wrangel Island polynya, that were associated with a stronger BSH and enhanced easterly flow across the region. The BSH also plays an important role in forcing the Beaufort Gyre, an oceanographic feature that is the Arctic Ocean's largest reservoir of freshwater [ Giles et al , 2012].…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, Serreze and Barrett [2011] did not identify any statistically significant trend in the BSH during any season, although there was some evidence of a recent amplification during the summer. Moore and Pickart [2012] noted that the size of the early summer Wrangel Island polynya has been increasing since the late 1990s and attributed this to a tendency for a strengthening of the easterly flow across the region resulting from a trend towards a more intense BSH.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the dipole is strongest in the winter months: December through March, and is weakest in the summer months: July through October. There is a spike in dipole strength in June, perhaps in relation to the seasonal opening of the Wrangel Island Polynya which typically opens in June (Moore & Pickart, 2012). It is evident in the winter that the poles are of approximately equal magnitude, while in June only the western pole is large.…”
Section: Resultsmentioning
confidence: 95%
“…The typical anti-cyclonic circulation induces easterly winds from the Beaufort Sea towards the Chukchi Sea which contribute to westward transport of sea ice toward Wrangel Island. Much of the ice is blocked by the island which contributes to the opening of a seasonal polynya to its north-west (Sverdrup, 1929;Cavalieri & Martin, 1994;Moore & Pickart, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4c, vertical fluxes are positive downwards) associated with warm southerly wind (observed at the Kap Morris Jesup weather station) caused the heat exchange from the atmosphere to ocean. This heat exchange may have created more heat into the ocean, which would contribute to the maintenance of the polynya and further affect the water mass transformation and deep water formation (Moore and Pickart, 2012).…”
Section: Sea Ice Drift Driven By Windmentioning
confidence: 99%